2023
DOI: 10.2147/opth.s403351
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Clinical Outcomes of Hydrophilic and Hydrophobic Versions of a Trifocal IOL with the Same Optical Design

Abstract: Purpose To show the visual and refractive outcomes in Asian eyes with cataract when bilaterally implanted with either a hydrophobic FineVision POD F GF or a hydrophilic FineVision POD F intraocular lens (IOL). Methods Forty-six patients were randomized to receive POD F GF or POD F IOLs. Visual and refractive outcomes were assessed up to 24 months post-surgery. Measurements included uncorrected-distance visual acuity, corrected-distance visual acuity (CDVA), distance-cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The analysis of the binocular defocus curve revealed an extended range of functional vision was provided with the refractive multi-segmented IOL evaluated, as in previous studies analysing the same IOL [7,8]. Speci cally, mean binocular distance-corrected visual acuity was over 0.20 logMAR for defocus levels from + 1.50 to -3.00 D. Alió and colleagues [7] reported in their series evaluating the Precizon Presbyopic IOL that it was able to provide a visual acuity of 0.16 logMAR or better for defocus levels between + 1.00 and − 2.50 D. All these visual outcomes were consistent with those provided by other modalities of presbyopia-correcting IOLs, such as hybrid IOLs combining an extended depth of focus (EDOF) and a diffractive multifocal pro le [13,14] or conventional trifocal diffractive IOLs [15][16][17]. Shin et al [13] reported that the distance-corrected visual acuity in the binocular defocus curve of 35 patients implanted with the Tecnis Synergy™ IOL was 0.11 logMAR or better for the range of defocus levels between + 0.50 and − 2.50 D. Burkhard Dick et al [15] found in a sample of 95 eyes implanted with the Tecnis Synergy IOL and in a sample of 52 eyes implanted with the diffractive trifocal IOL PanOptix that mean corrected-distance visual acuities at the 3-month binocular defocus curve were 0.10 logMAR or better for the defocus levels between + 0.50 and − 3.00 D. The good level of visual rehabilitation achieved with the evaluated IOL agreed with the high level of spectacle independence found (90%).…”
Section: Discussionmentioning
confidence: 68%
“…The analysis of the binocular defocus curve revealed an extended range of functional vision was provided with the refractive multi-segmented IOL evaluated, as in previous studies analysing the same IOL [7,8]. Speci cally, mean binocular distance-corrected visual acuity was over 0.20 logMAR for defocus levels from + 1.50 to -3.00 D. Alió and colleagues [7] reported in their series evaluating the Precizon Presbyopic IOL that it was able to provide a visual acuity of 0.16 logMAR or better for defocus levels between + 1.00 and − 2.50 D. All these visual outcomes were consistent with those provided by other modalities of presbyopia-correcting IOLs, such as hybrid IOLs combining an extended depth of focus (EDOF) and a diffractive multifocal pro le [13,14] or conventional trifocal diffractive IOLs [15][16][17]. Shin et al [13] reported that the distance-corrected visual acuity in the binocular defocus curve of 35 patients implanted with the Tecnis Synergy™ IOL was 0.11 logMAR or better for the range of defocus levels between + 0.50 and − 2.50 D. Burkhard Dick et al [15] found in a sample of 95 eyes implanted with the Tecnis Synergy IOL and in a sample of 52 eyes implanted with the diffractive trifocal IOL PanOptix that mean corrected-distance visual acuities at the 3-month binocular defocus curve were 0.10 logMAR or better for the defocus levels between + 0.50 and − 3.00 D. The good level of visual rehabilitation achieved with the evaluated IOL agreed with the high level of spectacle independence found (90%).…”
Section: Discussionmentioning
confidence: 68%
“…For the sample size calculation, the following parameters were used: continuous outcome, noninferiority trial, an α of 0.05; a power of 0.95; 2-sided test; an expected SD of outcome of 0.07 logMAR (based on clinical outcomes obtained by the same investigator on the spherical model of this IOL); and a noninferiority limit of 0.04 logMAR. 17 Using the Sealed Envelope Power calculator and to show noninferiority between the study group and the control cohort on monocular CDVA (first implanted eyes only), 80 eyes/patients were needed. 18 With an expected drop-out rate of 15%, a minimum number of 95 patients had to be recruited.…”
Section: Methodsmentioning
confidence: 99%
“…ИОЛ выполнена из гидрофобного мягкого акрила с УФ-фильтром, число Аббе -55, имеет заднюю ахроматическую дифракционную поверхность для усиления восприятия контрастности и эшелетт дизайн, который позволяет продлевать диапазон фокуса света [10][11][12]. В качестве сравнительных оценивались, в большинстве случаев, традиционные ТФИОЛ («PanOptix», «FineVison» и «Lisa tri 839MP») [13][14][15]. Во всех исследованиях, включенных в данный обзор, была выполнена двусторонняя имплантация.…”
Section: сравнительная оценка эдоф и тфиолunclassified